2010
DOI: 10.1016/j.physc.2010.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and superconductivity of europium

Abstract: We have calculated the electronic structure of Eu for the bcc, hcp, and fcc crystal structures for volumes near equilibrium up to a calculated 90 GPa pressure using the augmented-plane wave method in the local-density approximation. The frozen-core approximation was used with a semi-empirical shift of the f-states energies in the radial Schrödinger equation to move the occupied 4f valence states below the Γ 1 energy and into the core. This shift of the highly localized f-states yields the correct europium phas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, as we proceed from Ce to Tm, E F is within the very narrow f-bands and as a result DFT cannot find the appropriate minimum of the total energy. We have found that a reasonable equilibrium volume can be calculated for these materials by pushing the f-electrons into the core and use only the s-and d-electrons in the valence [17] [18]. For Yb and La the f-bands are clearly below E F and the calculated equilibrium volume is reasonable.…”
Section: Lanthanides (Yb and La)mentioning
confidence: 84%
“…However, as we proceed from Ce to Tm, E F is within the very narrow f-bands and as a result DFT cannot find the appropriate minimum of the total energy. We have found that a reasonable equilibrium volume can be calculated for these materials by pushing the f-electrons into the core and use only the s-and d-electrons in the valence [17] [18]. For Yb and La the f-bands are clearly below E F and the calculated equilibrium volume is reasonable.…”
Section: Lanthanides (Yb and La)mentioning
confidence: 84%
“…We note that Nixon and Papaconstantopoulos [22] have recently calculated the electronic structure of Eu for the bcc, hcp, and fcc structures to 90 GPa pressure using the augmented-plane-wave method in the local-density approximation. Using a simple Debye model to approximate the change in the average phonon frequency under pressure, they find that in both the bcc and hcp phases Eu becomes superconducting above 60 GPa, increasing to a value near 2 K at 80 GPa, in agreement with experiment [14].…”
Section: Results Of Structure Searchmentioning
confidence: 99%